A Novel Sulfone Derivative Controls Lasiodiplodia theobromae in Tea Leaf Spot by Reducing the Ergosterol Content - Xingtao Bao; Rui Yang; Shilong Jiang; Jinping Zhao; Delu Wang; Dongxue Li; Xian Wu; Baoan Song; Zhuo Chen (Molecular Plant-Microbe Interactions, 2021)
Diseases caused by fungi can affect the quality and yield of the leaves of tea [Camellia sinensis (L.) Kuntze]. At present, the availability of highly effective and safe fungicides for controlling tea plants remains limited. The objectives of this study were to identify novel compounds with antifungal activities and to determine their molecular mechanisms. A series of sulfone compounds containing 1,3,4-oxadiazole were evaluated in China for their antifungal activities against several pathogens causing foliar diseases and high production losses. Transcriptomics and bioinformatics were used to analyze the differentially expressed genes of Lasiodiplodia theobromae treated with a representative compound, jiahuangxianjunzuo (JHXJZ). Moreover, the effects of JHXJZ on ergosterol content, membrane permeability, cell structure, and seven key genes involved in the ergosterol biosynthetic pathway were investigated. JHXJZ had a strong antifungal activity against L. theobromae in vitro, with an effective concentration giving 50% inhibition of 3.54 ± 0.55 μg/ml, and its curative efficacies on detached tea leaves reached 41.78% at 100 μg/ml. JHXJZ upregulated 899 genes (P < 0.05) and downregulated 1,185 genes (P < 0.05) in L. theobromae. These genes were found to be associated with carbohydrate metabolic processes, which are closely related to steroid biosynthesis in the Kyoto Encyclopedia of Genes and Genomes pathways. Because JHXJZ regulates the key genes of sterol biosynthesis, it decreased the ergosterol content, increased cell-membrane permeability, changed the cellular structure, enhanced the roughness of the surface of the hyphae, and resulted in degradation of the hyphal nuclei and necrosis of the hyphal cytoplasm. Our study demonstrates that JHXJZ is a fungicide with a novel mechanism of action that differs from that of triazole fungicides. JHXJZ has potential for applications in controlling tea plant diseases.[Graphic: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.